Konsep Produksi dalam Perspektif Baqir Shadr - Nurdin, Muh. Syarif (El-Barka Journal of Islamic Economics and Business, 2019)
Abstract: The purpose of this study is to; 1) knowing the concept of production according to Baqir Sadr, 2) knowing Baqir Sadr's criticism of the concept of production of capitalism. The type of research used is library research or library research that examines the concept of production in the view of Baqir Sadr with the literature relating to the object of study. The results of the study show that the thing that makes the concepts of production of capitalism, socialism, and Islam different is due to the motives of the actors in this case the producers in achieving their goals which are influenced by the economic doctrine they adhere to. To develop production, there are two tools that can be taken, namely intellectual means as paradigama which are used as a way of life for each producer so that they will shape their ethics and morality in production. The second is a legal facility which is a facility that is used as a rule in production which consists of maximizing the use of land into productive land and eliminating usury practices in production where the use of interest is included. Baqir Sadr's criticism of the concept of production of capitalism is the maximum benefit. So that production is only based on demand which is influenced by purchasing power. While high purchasing power is only possessed by a certain group, making the poor have no influence in determining the demand for certain commodities. Ø§Ù„Ù…Ù„Ø®Øµ: : Ù„ØºØ±Ø¶ Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ: 1) Ù…Ø¹Ø±ÙØ© Ù…ÙÙ‡ÙˆÙ… Ø§Ù„Ø¥Ù†ØªØ§Ø¬ Ø¨Ø±Ø¢ÙŠ Ø¨Ø§Ù‚Ø± Ø§Ù„ØµØ¯Ø± ØŒ 2) Ù…Ø¹Ø±ÙØ© Ù†Ù‚Ø¯ Ø¨Ø§Ù‚Ø± Ø§Ù„ØµØ¯Ø± Ù„Ù…ÙÙ‡ÙˆÙ… Ø§Ù„Ø¥Ù†ØªØ§Ø¬ Ù„Ù„Ø±Ø£Ø³Ù…Ø§Ù„ÙŠØ©.Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù… ÙÙŠ Ù‡Ø°Ø§Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø¨ØØ« Ø§Ù„Ù…ÙƒØªØ¨Ø© Ø£Ùˆ Ø¨ØØ« Ø§Ù„Ù…ÙƒØªØ¨Ø© Ø§Ù„Ø°ÙŠ ÙŠØ¯Ø±Ø³ Ù…ÙÙ‡ÙˆÙ… Ø§Ù„Ø¥Ù†ØªØ§Ø¬ Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø¨Ø§Ù‚Ø± Ø§Ù„ØµØ¯Ø± Ù…Ø¹ Ø§Ù„Ø£Ø¯Ø¨ÙŠØ§Øª Ø§Ù„Ù…ØªØ¹Ù„Ù‚Ø© Ø¨Ù…ÙˆØ¶ÙˆØ¹ Ø§Ù„Ø¯Ø±Ø§Ø³Ø©. ØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ø§Ù„Ø´ÙŠØ¡ Ø§Ù„Ø°ÙŠ ÙŠØ¬Ø¹Ù„ Ù…ÙØ§Ù‡ÙŠÙ… Ø¥Ù†ØªØ§Ø¬ Ø§Ù„Ø±Ø£Ø³Ù…Ø§Ù„ÙŠØ© ÙˆØ§Ù„Ø§Ø´ØªØ±Ø§ÙƒÙŠØ© ÙˆØ§Ù„Ø¥Ø³Ù„Ø§Ù… Ù…Ø®ØªÙ„ÙØ© Ù‡Ùˆ Ø¯ÙˆØ§ÙØ¹ Ø§Ù„Ø¬Ù‡Ø§Øª Ø§Ù„ÙØ§Ø¹Ù„Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„ØØ§Ù„Ø© Ø§Ù„Ù…Ù†ØªØ¬ÙˆÙ† ÙÙŠ ØªØÙ‚ÙŠÙ‚ Ø£Ù‡Ø¯Ø§ÙÙ‡Ù… Ø§Ù„ØªÙŠ ØªØªØ£Ø«Ø± Ø¨Ø§Ù„Ù…Ø°Ù‡Ø¨ Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠ Ø§Ù„Ø°ÙŠ ÙŠÙ„ØªØ²Ù…ÙˆÙ† Ø¨Ù‡. Ù„ØªØ·ÙˆÙŠØ± Ø§Ù„Ø¥Ù†ØªØ§Ø¬ ØŒ Ù‡Ù†Ø§Ùƒ Ø£Ø¯Ø§ØªØ§Ù† ÙŠÙ…ÙƒÙ† Ø§ØªØ®Ø§Ø°Ù‡Ù…Ø§ ØŒ ÙˆÙ‡Ù…Ø§ Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ÙÙƒØ±ÙŠØ© Ù…Ø«Ù„ Ø§Ù„Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„Ø°ÙŠ ÙŠØ³ØªØ®Ø¯Ù… ÙƒÙˆØ³ÙŠÙ„Ø© Ù„Ù„ØÙŠØ§Ø© Ù„ÙƒÙ„ Ù…Ù†ØªØ¬ ØØªÙ‰ ÙŠØªÙ…ÙƒÙ†ÙˆØ§ Ù…Ù† ØªØ´ÙƒÙŠÙ„ Ø£Ø®Ù„Ø§Ù‚ÙŠØ§ØªÙ‡Ù… ÙˆØ£Ø®Ù„Ø§Ù‚Ù‡Ù… ÙÙŠ Ø§Ù„Ø¥Ù†ØªØ§Ø¬. ÙˆØ§Ù„Ø«Ø§Ù†ÙŠ Ù‡Ùˆ Ù…Ø±ÙÙ‚ Ù‚Ø§Ù†ÙˆÙ†ÙŠ ÙˆÙ‡Ùˆ Ù…Ø±ÙÙ‚ ÙŠØ³ØªØ®Ø¯Ù… ÙƒÙ‚Ø§Ø¹Ø¯Ø© ÙÙŠ Ø§Ù„Ø¥Ù†ØªØ§Ø¬ ÙˆØ§Ù„Ø°ÙŠ ÙŠØªÙƒÙˆÙ† Ù…Ù† ØªØ¹Ø¸ÙŠÙ… Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£Ø±Ø§Ø¶ÙŠ ÙÙŠ Ø§Ù„Ø£Ø±Ø§Ø¶ÙŠ Ø§Ù„Ù…Ù†ØªØ¬Ø© ÙˆØ§Ù„Ù‚Ø¶Ø§Ø¡ Ø¹Ù„Ù‰ Ù…Ù…Ø§Ø±Ø³Ø§Øª Ø§Ù„Ø±Ø¨Ø§ ÙÙŠ Ø§Ù„Ø¥Ù†ØªØ§Ø¬ ØÙŠØ« ÙŠØªÙ… ØªØ¶Ù…ÙŠÙ† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ÙØ§Ø¦Ø¯Ø©. Ù†Ù‚Ø¯ Ø¨Ø§Ù‚Ø± Ø§Ù„ØµØ¯Ø± Ù„Ù…ÙÙ‡ÙˆÙ… Ø¥Ù†ØªØ§Ø¬ Ø§Ù„Ø±Ø£Ø³Ù…Ø§Ù„ÙŠØ© Ù‡Ùˆ Ø£Ù‚ØµÙ‰ ÙØ§Ø¦Ø¯Ø©. Ø¨ØÙŠØ« ÙŠØ¹ØªÙ…Ø¯ Ø§Ù„Ø¥Ù†ØªØ§Ø¬ ÙÙ‚Ø· Ø¹Ù„Ù‰ Ø§Ù„Ø·Ù„Ø¨ Ø§Ù„Ø°ÙŠ ÙŠØªØ£Ø«Ø± Ø¨Ø§Ù„Ù‚ÙˆØ© Ø§Ù„Ø´Ø±Ø§Ø¦ÙŠØ©. ÙÙŠ ØÙŠÙ† Ø£Ù† Ø§Ù„Ù‚ÙˆØ© Ø§Ù„Ø´Ø±Ø§Ø¦ÙŠØ© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ù„Ø§ ØªÙ…Ù„ÙƒÙ‡Ø§ Ø¥Ù„Ø§ Ù…Ø¬Ù…ÙˆØ¹Ø© Ù…Ø¹ÙŠÙ†Ø© ØŒ ÙØ¥Ù† Ø¬Ø¹Ù„ Ø§Ù„ÙÙ‚Ø±Ø§Ø¡ Ù„ÙŠØ³ Ù„Ù‡Ù… Ø£ÙŠ ØªØ£Ø«ÙŠØ± ÙÙŠ ØªØØ¯ÙŠØ¯ Ø§Ù„Ø·Ù„Ø¨ Ø¹Ù„Ù‰ Ø³Ù„Ø¹ Ù…Ø¹ÙŠÙ†Ø©. Abstrak: Tujuan penelitian ini adalah untuk; 1) mengetahui konsep produksi menurut Baqir Shadr, 2) mengetahui kritik Baqir Shadr terhadap konsep produksi kapitalisme. Jenis  penelitian yang digunakan ialah penelitian pustaka atau library research yang mengkaji konsep produksi dalam pandangan Baqir Shadr  dengan literature-literatur yang berkaitan dengan obyek kajian. Hasil penelitian menunjukkan bahwa hal yang membuat konsep produksi kapitalisme, sosialisme, dan Islam berbeda disebabkan oleh motif pelaku dalam hal ini produsen dalam mencapai tujuannya yang dipengaruhi oleh doktrin ekonomi yang dianutnya. Untuk mengembangkan produksi maka ada dua sarana yang dapat ditempuh yaitu sarana intelektual sebagai paradigama yang dijadikan way of life bagi setiap produsen sehingga akan membentuk etika dan moralitasnya dalam berproduksi. Yang kedua adalah sarana hukum yang merupakan sarana yang dijadikan sebagai aturan dalam produksi yang terdiri dari pemaksimalan penggunaan tanah menjadi tanah produktif dan  penghapusan praktik riba dalam produksi dimana penggunaan bunga termasuk didalamnya. Adapun kritik Baqir Shadr terhadap konsep produksi kapitalisme adalah keuntungan maksimum. Sehingga produksi hanya didasarkan pada permintaan yang dipengaruhi oleh daya beli. Sedangkan daya beli yang tinggi hanya dimiliki oleh sekelompok tertentu membuat orang miskin tidak mempunyai pengaruh dalam menentukan permintaan komoditas tertentu.